The Effects of Parenting Style and Adolescent Character on Adolescent Spirituality During The Pandemic - Lidia Susanti; Candra Tarigan (Jurnal Jaffray, 2021)
Parenting adolescents during the pandemic is a considerably challenging endeavour. The parenting style of families constitutes a crucial factor in the shaping of adolescent characters and spirituality. Family is primary socialization through which adolescents develop their character and spirituality. Parenting patterns in adolescents have a significant impact on their personality and spirituality. This is evidenced in the love of God. This research employed an ex post facto design. The results revealed that parenting styles families adopted during the pandemic impacted adolescent characters and spirituality. The data analysis showed an interaction between parenting style variables and adolescent characters and the spirituality of Batak adolescents indicated by the R square value of 97.1%.